Membangun Kesadaran Budaya Generasi Muda Melalui Pelatihan Seni Tambua dan Tari di Koto Panjang - Rido Putra; Julira Mirna; Fatimah Azzahra; Gina Mufidah Nasywa; Siti Aminah; Putri Syaharani (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
This study examines efforts to build cultural awareness among young people through tambua and dance training in Koto Panjang. Traditional arts, particularly tambua and Minangkabau dance, play a vital role as community identity and symbols of regional glory. The preservation and regeneration of these arts require strategic interventions to transfer cultural values to the younger generation. A descriptive qualitative research method was used with a participatory observation approach and literature review to analyze the training process. Data were collected through direct observation during the Community Service Program (KKN) and a review of relevant literature. The results showed that the structured training model, encompassing history, philosophy, techniques, and simulations of traditional performances, was effective in engaging young people in Koto Panjang. This training not only improved participants' technical skills in tambua playing and dancing but also fostered a deeper understanding of Minangkabau cultural values such as mutual cooperation and discipline. Identified positive impacts include increased self-confidence, sustainable cultural regeneration, increased social participation, and contributions to the local economy through cultural tourism. This training serves as a powerful model for preserving cultural heritage and empowering young people as agents of tradition.